Overview of Network Topology in Hospital Management System - Fenska Seipalla; Nadia Liem; Deorina Siregar; Ardhin Martdana; Vip Paramarta (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Modern hospital administration systems rely significantly on information technology, which includes patient data, medicine inventory management, medical equipment, and more.  Understanding network topology is crucial in hospital system management to ensure that the network infrastructure chosen is consistent with the hospital's operational goals and objectives. The method of writing a review of this article is based on the search of the relevant literature to the main problem of the review. The findings compare each network topology's advantages and disadvantages for implementation in a hospital management system. In its network design, hospitals must consider a number of challenges and concerns. First, data integration between a hospital's internal systems must be smooth and seamless in order to provide appropriate and effective patient care. Second, data security must be prioritized, with contemporary security technology such as firewalls and data encryption used. Furthermore, to ensure continuous service availability, network maintenance must be planned and executed effectively. Finally, profit optimization entails selecting the appropriate equipment and employing cost-effective management practices to support long-term hospital operations. In the end, selecting a stable network topology is critical to achieving high patient service satisfaction.